Whole-Genome Sequencing of Mexican Strains of Anaplasma marginale: An Approach to the Causal Agent of Bovine Anaplasmosis - Fernando Martínez-Ocampo; Rosa Estela Quiroz-Castañeda; Itzel Amaro-Estrada; Edgar Dantán-González; Jesús Francisco Preciado de la Torre; Sergio Rodríguez-Camarillo (International Journal of Genomics)
Anaplasma marginale is the main etiologic agent of bovine anaplasmosis, and it is extensively distributed worldwide. We have previously reported the first genome sequence of a Mexican strain of A. marginale (Mex-01-001-01). In this work, we report the genomic analysis of one strain from Hidalgo (MEX-14-010-01), one from Morelos (MEX-17-017-01), and two strains from Veracruz (MEX-30-184-02 and MEX-30-193-01). We found that the genome average size is 1.16-1.17 Mbp with a GC content close to 49.80%. The genomic comparison reveals that most of the A. marginale genomes are highly conserved and the phylogeny showed that Mexican strains cluster with Brazilian strains. The genomic information contained in the four draft genomes of A. marginale from Mexico will contribute to understanding the molecular landscape of this pathogen.